Mass spectrometry-based identification reveals the polymicrobial nature of canine urinary tract infections - Rodrigues Paschoal, Natália [UNESP]; Ramos Portilho, Fábio Vinícius [UNESP]; Oliveira de Almeida, Beatriz [UNESP]; Fagali Arabe Filho, Marcelo [UNESP]; Rodrigues, Carolina Aparecida [UNESP]; Spessotto Bello, Thaís [UNESP]; de Lima Paz, Patrik Júnior [UNESP]; Paganini Listoni, Fernando José [UNESP]; Garcia Ribeiro, Márcio [UNESP] (Springer Nature, 2025)
Canine urinary tract infections (UTIs) are common in veterinary practice and often have a complex etiology. Typically, diagnoses rely on classical phenotypic tests or are limited to identifying the genus of the pathogen. Treatments are frequently administered without prior in vitro antimicrobial susceptibility testing. This study analyzed 389 urine samples from dogs with clinical signs of UTI, collected by cystocentesis, through microbiological culture. Species-level identification of bacteria and yeasts was performed using mass spectrometry, while bacterial isolates underwent antimicrobial susceptibility testing via the disk diffusion method. Of the 389 samples, 170 (43.7%) showed microbial growth, with 192 microorganisms identified. Among these, 98.4% (189/192) were bacteria, and 1.6% (3/192) were fungi/yeasts. The predominant pathogens included Enterobacteria (116/192 = 60%), enterococci (26/192 = 13.5%), and staphylococci (24/192 = 12.5%). Novel pathogens, such as Lactobacillus murinus and Stenotrophomonas maltophilia, were identified as primary agents of canine UTIs. Coinfections commonly involved E. coli with either E. faecalis (5/21 = 23.8%) or S. canis (4/21 = 19%). Amoxicillin/clavulanic acid was the most effective antimicrobial (≥ 70%), followed by amikacin and marbofloxacin (≥ 60%). Observed antimicrobial resistance rates included enterobacteria (18%), enterococci (> 40%), staphylococci (18%), streptococci (30%), Pseudomonas aeruginosa (60%), and other organisms (> 30%). Multidrug resistance affected 18% (34/189) of bacterial isolates. This study highlights the polymicrobial nature of canine UTIs and emphasizes concerns about multidrug-resistant bacteria. These findings contribute to improving molecular diagnostics and monitoring antimicrobial resistance in domestic animals, a critical global issue.
Keywords: Bacterial multidrug resistance; Canine microbial etiology; Canine urinary infections; MALDI-TOF MS